2014
DOI: 10.1590/1516-635x1604359-366
|View full text |Cite
|
Sign up to set email alerts
|

Pathological, immunohistochemical, and molecular findings in commercial laying hens and in backyard chickens naturally infected with the infectious laryngotracheitis virus

Abstract: KeywordsAvian infectious laryngotracheitis, conventional PCR, histopathology, immunohistochemistry, laying hen.Submitted: November/2013 Approved: June/2014 ABSTRACT Seventy-eight chickens from a very high poultry density (approximately eight million) region and twelve backyard chickens from neighboring areas were analyzed by histopathology and additional techniques for the presence of the infectious laryngotracheitis virus. The virus distribution was determined in different tissues using immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Preis et al [11] detected 70% positivity in the larynx and trachea tissues, and 53.8% positive results in the lungs in the field study immunohistochemically. They reported that these positive reactions were intracytoplasmic located in the mucosa and desquamated epithelial cells in the larynx and trachea, and parabronchial epithelium in the lung.…”
Section: +5 (Very Serious) Lesions the Epithelial Layer Is Completelmentioning
confidence: 92%
See 3 more Smart Citations
“…Preis et al [11] detected 70% positivity in the larynx and trachea tissues, and 53.8% positive results in the lungs in the field study immunohistochemically. They reported that these positive reactions were intracytoplasmic located in the mucosa and desquamated epithelial cells in the larynx and trachea, and parabronchial epithelium in the lung.…”
Section: +5 (Very Serious) Lesions the Epithelial Layer Is Completelmentioning
confidence: 92%
“…Immunohistochemical methods have recently been used to diagnose ILT by many researchers [8,9,11,[32][33][34] . IHC methods have been shown to be helpful for diagnosing ILT when macroscopical and histopathological findings are not possible [35] .…”
Section: +5 (Very Serious) Lesions the Epithelial Layer Is Completelmentioning
confidence: 99%
See 2 more Smart Citations
“…Microscopic examination of invaded tissues stained with hematoxylin and eosin reveals eosinophilic cytoplasmic inclusions, which are also detected with fluorescent antibodies and immunohistochemical methods (Ali et al, 2016;Bande et al, 2016). Viral particles with a typical virus morphology are determined by transmission electron microscopy with negative coloration, as well as in ultrathin sections of lesions (Preis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%